2021
DOI: 10.3390/children8090810
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Life-Course Psychosocial Stress and Kidney Function

Abstract: Increased exposure to maternal psychosocial stress during gestation and adverse neonatal environments has been linked to alterations in developmental programming and health consequences in offspring. A programmed low nephron endowment, among other altered pathways of susceptibility, likely increases the vulnerability to develop chronic kidney disease in later life. Our aim in this scoping review was to identify gaps in the literature by focusing on understanding the association between life-course exposure to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 76 publications
(159 reference statements)
0
1
0
Order By: Relevance
“…Studies have indicated besides the well-known risk factors for CKD, such as age, smoking, hypertension, and diabetes (5,6), the early-life stressors including adverse childhood experiences (ACEs) may be a potential contributor to the risk of CKD (7)(8)(9). ACEs refer to a range of intensive stressors that occur before the age of 18 that have been shown to be associated with the risk of chronic diseases and early mortality (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated besides the well-known risk factors for CKD, such as age, smoking, hypertension, and diabetes (5,6), the early-life stressors including adverse childhood experiences (ACEs) may be a potential contributor to the risk of CKD (7)(8)(9). ACEs refer to a range of intensive stressors that occur before the age of 18 that have been shown to be associated with the risk of chronic diseases and early mortality (10,11).…”
Section: Introductionmentioning
confidence: 99%